2016
DOI: 10.2147/cwcmr.s85463
|View full text |Cite
|
Sign up to set email alerts
|

Preventing, minimizing, and managing pain in patients with chronic wounds: challenges and solutions

Abstract: Abstract:It is widely known that pain frequently accompanies certain types of chronic wounds, most notably arterial insufficiency ulcers, venous leg ulcers, and diabetic foot ulcers; however, until recently, pain associated with chronic wounds has not received much attention. A limited number of studies have explored the impact of painful wounds on the quality of life. Nonetheless, these early works have brought wound-related pain (WRP) to the forefront and highlighted the importance of pain assessment and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
11
2
Order By: Relevance
“…It has been reported that within 5 years after achieving wound closure, between 70 and 100% of these healed ulcers will re-open and require additional ulcer management treatments [9]. DFUs substantially reduce patients' quality of life, are often painful, and adversely affect mobility and sleep [10][11][12][13]. Furthermore, ulcers are significantly correlated with time lost from work, job loss and high rates of adverse effects and serious adverse events [14,15].…”
mentioning
confidence: 99%
“…It has been reported that within 5 years after achieving wound closure, between 70 and 100% of these healed ulcers will re-open and require additional ulcer management treatments [9]. DFUs substantially reduce patients' quality of life, are often painful, and adversely affect mobility and sleep [10][11][12][13]. Furthermore, ulcers are significantly correlated with time lost from work, job loss and high rates of adverse effects and serious adverse events [14,15].…”
mentioning
confidence: 99%
“…Thus, care should be provided in a warm and calm environment that will allow the patient to relax. 31 Wound debridement often presents a challenge in PG because of its feature of pathergy, or exacerbation in response to incidental or iatrogenic trauma. 39 For this reason, surgical debridement is not generally recommended.…”
Section: Local Treatmentmentioning
confidence: 99%
“…Another important aspect of treatment is the pain, which should be addressed depending on the intensity of pain, initially with oral administration of acetaminophen and nonsteroidal anti‐inflammatory drugs for nociceptive pain (gnawing, aching, tender, and/or throbbing pain), then as necessary mild opioids such as codeine, then strong opioids such as morphine, until the patient is free of pain 30 . The use of opioids for the treatment of noncancer pain remains controversial, thus, clinicians need to be careful to minimise abuse and to treat pain effectively 31 Initial treatment of neuropathic pain (burning, stinging, shooting, or stabbing) can be managed with gabapentin and pregabalin, along with nortriptyline at night to facilitate sleep 32…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The former leads to addiction, dependence, and tolerance while the latter causes a ceiling effect. 10,11 To overcome the issue, topical anesthetics are widely used to numb the skin and to relive pain in medical and surgical procedures in anesthesia, ophthalmology, otorhinolaryngology, dentistry, urology, and aesthetic surgery. Among topical anesthetics, lidocaine, tetracaine, benzocaine, and prilocaine in a cream, ointment, or gel are commonly available as prescription and/or over-the-counter (OTC) products.…”
Section: Introductionmentioning
confidence: 99%